Technology Adoption and Change Management in Smart Manu-facturing Industries - Ibragimov Ulmas Rakhmanovich; Lalit Sachdeva (Malikussaleh University, Aceh, Indonesia, 2025)
The benefits of the Internet of Things are widely acknowledged. Nonetheless, a number of articles and white papers continue to uncover security flaws in IoT, which is a major worry that the industry finds unacceptable. It can be challenging to safely connect these systems to external networks. Since the study focuses on technological acceptance, it's critical to comprehend additional factors that may influence IoT adoption. To identify the elements that impact behavioural intentions to use technology to control user behaviour, a number of theoretical models have been examined. Since academics have provided a variety of explanations for why the adoption of IoT has been hampered in various works of literature, a comprehensive study that examines all of the factors at once and presents accurate data is required. Therefore, determining the factors limiting the adoption of IoT in the manufacturing sector in and around Mumbai is the issue this study attempts to solve. The study examines supportive conditions, performance expectancy, effort expectancy, and security awareness. The study will investigate how these constructions are affected by large, medium, and small organisations. The final study will assist company managers, IoT manufacturers, and service providers in boosting IoT adoption.